Development of a computer service for assessing and analysing the readiness of freestyle athletes - Zdanovich, O.; Zebzeev, V.; Paramonova, N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to create a special computer service for automating the assessment and analysis of freestyle skiers' preparedness.